Being, Substance and Form in Aristotle’s Metaphysics (Philosophy and Progress, 2019)
The concepts of ‘being‘, ‘substance‘ and ‘form‘ are central to Aristotle‘s metaphysics. According to him, there are different modes of being, and of all these different modes of being, substance is the primary mode of being, and First Philosophy is especially concerned with the mode of being which belongs to substances. Again, he tries to give an analysis of what a substance is in terms of the concept of form, and claims that it is essence or form that may be called substance in the truest and fullest sense. Thus we see that the concepts of ‘being‘, ‘substance‘ and ‘form‘ are intimately related. This paper is an attempt to analyze clearly what Aristotle means by these three important concepts.Philosophy and Progress, Vol#61-62; No#1-2; Jan-Dec 2017 P 43-52